The Influence of Strain Rate on the Plasticity of Steel Sheets - Michel, Jan; Bursak, Marian (Communications - Scientific letters of the University of Zilina, 2010)
The paper analyses the influence of strain rate on the behaviour of un-alloyed steels with Re 210–550 MPa in the deformation process. It presents and analyses the results of the influence of the strain rates ranging from 103 to 2.5 . 102 s1 on the yield point, tensile strength, elongation and reduction of area. It analyses the non-homogeneity of development of plastic deformation from both, the macroscopic and microscopic points of view, as well as the influence of the strain rate on the development of plastic deformation. Since the intensity of the influence of the strain rate on the properties of materials depends on their internal structure, the tested steels are divided into three groups based on their yield point and yield point of tensile strength ratio.